The Classroom and New Learning: An Investigation of Interrelationship Among Pre-Service Teachers’ Statistical Reasoning, Attitude Towards Statistics, and Learning Approach on Achievement in Statistics - Eluwa, Obukohwo I; Asim, Alice E; Eluwa, Akubuike N; Abang, K. Bekom (Richtmann Publishing, 2011)
The study sought to investigate inter- relationships amongst statistical reasoning, attitude towards statistics, learningapproach and achievement in educational statistics. Ex-post facto research design was adopted for the study. The sampleconsisted of 358 (114 males and 244 females) fourth year pre-service teachers from University of Calabar and Port Harcourt inthe South-South Geopolitical Zone of Nigeria. The data for the study was collected using two instruments named: StatisticalReasoning Learning Approach Questionnaire (SRALAQ), and the Educational Statistics Test (EST). Analyses of data werecarried out using multiple regression and path analysis. The results showed that: there is a significant composite effect of preserviceteachers’ statistical reasoning, attitude towards statistics and learning approach on achievement in educational statistics;and there are significant paths through which the independent variables determine achievement in educational statistics. Thestrongest of these paths is between statistical reasoning and learning approach and attitude towards statistics and learningapproach. Learning approach was found to be a significant direct predictor (β = .225, t = 2.581, p< 0.010) of pre-serviceteachers’ achievement in educational statistics at 0.05 level of significance. A meaningful causal model which could be used toexplain the causal relationship amongst the variables in the study also emanated. The causal model showed that pre-serviceteachers’ achievement in educational statistics could be explained directly and indirectly. The direct effect was 81.45% while theindirect effect was 18.55%. The magnitudes of the effects of the predictive variables in the study in order of their importance are0.429 for learning approach, 0.151 for statistical reasoning and -0.036 for attitude towards statistics. The implications of theresearch findings are addressed.